Preparation and Study on Electrochemical Performance of High-Rate LiFePO4/C Cathode Material - Ma, Zhi-Peng; Shao, Guang-Jie; Wang, Wei; Zhang, Chun-Ying (Asian Journal of Chemistry, 2013)
Carbon-coated LiFePO4 was synthesized by secondary ball-milling method. The structure of the material was systematically studied by X-ray diffraction and field-emission scanning electron microscopy. The particle size of the obtained LiFePO4/C composites was less than 300 nm and the tap density of the LiFePO4/C composites was 1.82 g/cm3. The electrochemical performance of the material was examined by cyclic voltammetry, electrochemical impedance spectra and constant current charge-discharge testing. The average discharge capacities of the LiFePO4/C composites were 133.4, 125.6, 114.2 and 94 mAh/g at rates of 1C, 2C, 5C and 10C, respectively. Even at 20C rate, the LiFePO4/C composites also showed the average discharge capacity of 81.3 mAh/g.